Postextrasystolic Blood Pressure Potentiation Predicts Poor Outcome of Cardiac Patients. Issue 3 (3rd June 2014) - Sinnecker, Daniel; Dirschinger, Ralf J.; Barthel, Petra; Müller, Alexander; Morley‐Davies, Adrian; Hapfelmeier, Alexander; Dommasch, Michael; Huster, Katharina M.; Hasenfuss, Gerd; Laugwitz, Karl‐Ludwig; Malik, Marek; Schmidt, Georg
Abstract : Background: Postextrasystolic blood pressure potentiation (PESP), the pulse wave augmentation after an extrasystolic beat, is typically enhanced in heart failure (HF) patients. This study prospectively tested the association of PESP and mortality in cardiac patients. Methods and Results: Consecutive patients (n=941; mean age, 61 years; 19% female) presenting with acute myocardial infarction were enrolled between May 2000 and March 2005 and followed up until August 2010. The main study outcome was 5‐year all‐cause mortality. Patients underwent noninvasive 30‐minute recordings of ECG and continuous blood pressure. PESP presence was based on the ratio between the first postectopic pulse wave amplitude and the mean of the subsequent 9 pulse wave amplitudes. A ratio above 1 was prospectively defined as PESP present. Ventricular premature complexes (VPCs) suitable for PESP quantification were present in recordings of 220 patients. PESP was present in 62 of these patients. Patients without suitable VPCs were classified as PESP absent. During the follow‐up, 72 patients died. Among the 220 patients in whom PESP was measurable, 27 died. Under univariable analysis, PESP was a significant predictor of death ( P <0.001) as were GRACE score ( P <0.001), left ventricular ejection fraction (LVEF) ( P <0.001), and the number of recorded VPCs ( P <0.001). Under multivariable analysis, PESP ( P <0.001), GRACE score ( P <0.001), and LVEF ( P =0.001) were independently associated with outcome. The combination of PESP presence and LVEF ≤35% identified a subgroup of patients with a particularly high mortality of 46.7%. Separate validation reproduced the finding in an unrelated population of 146 HF patients. Conclusions: PESP, which likely reflects abnormalities of myocardial calcium cycling, predicts the mortality risk in postinfarction patients. Clinical Trial Registration: URL:ClinicalTrials.gov . Unique identifier: NCT00196274.